Sammlungsverbleib (Dipteren-Kollektion Walter Peller). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1970)
There is given an information about the location of the Diptera collection of Walter Peller which now is located together with Father Strobl's collections in the Museum of Natural History Admont (Austria). Details of species and specimens will be published later in this journal.